Pemanfaatan Seduhan Daun Ashitaba dengan Simvastatin dalam Menurunkan Kadar LDL Tikus Putih Jantan Strain Wistar - Ernawati, Ernawati; Widjaja, Theresia Ratnasari (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2018)
High levels of blood cholesterol or hypercholesterolemia is an important risk factor for a cardiovascular disease. In order to overcome this problem, giving statins drug such as simvastatin is an intervention that is often applied. Besides using this drug, it can also be accompanied by consuming herbal plants which is Ashitaba leaves (Angelica keiskei). It contains Chalcones which demonstrates anti tumour property and also antioxidant activity that can lower cholesterol levels, especially LDL in the blood. This study aimed to investigate the effect of Ashitaba leaves (Angelica keiskei) steeping administration in assisting simvastatin drugs to decrease the levels of Low Density Lipoprotein (LDL) in the blood serum of male white rats Strain wistar (Rattus Norvegicus) with hypercholesterolemia. The population for this study was male white rats Strain wistar (Rattus Norvegicus) with samples taken in this study were 33 white rats. Data analysis for this study is using One Way Anova test.The result showed that supplementation of simvastatin treatment using steeping Ashitaba leaves might slightly reduce LDL level among male white rats Strain wistar (Rattus Norvegicus) with hypercholesterolemia. However, the result demonstrated not significant different.Â  Â To assist simvastatin drugs in lowering LDL levels in male white rats Strain wistar (Rattus Norvegicus) which is made to be hypercholesterolemia can lower LDL levels slightly but not significantly (p-value = 0,177) which is >a (0,05).